Addressing new demands on network security. (October 2015) - Hof, Jan
Abstract : Maintaining security over IT networks, regardless of an organisation's size or market sector, has become a much tougher challenge over the past few years, ever since once-solid perimeters turned into Swiss cheese and classic security tools became insufficient in dealing with contemporary demands. One prominent example is the North Korean attack on Sony Pictures Entertainment in December 2014. 1 That incident showed that even big players with large security budgets have problems maintaining their networks. Maintaining security over IT networks has become a much tougher challenge over the past few years. A key reason is unremitting change in the threat landscape.